Epidemiology of Rotavirus Diarrhoea in Children and Adults Presenting with Acute Gastroenteritis at a Tertiary Care Hospital in Northern India: A Cross-sectional Study - Aarsi Aarsi; Loveena Oberoi; Shailpreet Kaur Sidhu; Manmeet Kaur Sodhi; Tavishi Oberoi (Journal of Clinical and Diagnostic Research)
Introduction: Rotavirus is an important cause of severe diarrhoea in children under five years of age, accounting for approximately 78,000 deaths annually in this age group. The magnitude of acute gastroenteritis caused by rotavirus is often underestimated due to the lack of investigations into these cases. Although rotavirus disease is less common in adults, it can occur, possibly because of contact with children who have rotavirus gastroenteritis. Aim: To assess the current trend of the disease in both children as well as adults presenting with acute diarrhoea. Materials and Methods: This cross-sectional study was conducted over a period of one year (January 2023 to January 2024). A total of 185 stool samples were collected from children under five years of age and adults over 18 years presenting with acute diarrhoea at the outpatient and inpatient departments of Guru Nanak Dev Hospital (GNDH), Amritsar, Punjab, India. Commercially available Enzyme Linked Immunosorbent Assay (ELISA) kits were used to detect the VP6 antigen of Group A rotavirus in the stool samples of the patients. The data collected were analysed using Statistical Package for the Social Sciences (SPSS), and relevant conclusions were drawn. Results: Out of the 185 samples collected, 32 samples (17.3%) tested positive for rotavirus antigen. Vaccinated children experienced milder disease compared to unvaccinated ones. Non breastfed infants showed a higher detection rate of rotavirus, with 20 children (80%) testing positive compared to their breastfed counterparts. The rural-urban distribution indicated a greater burden in rural areas, with 16 children (64%) affected. Conclusion: This study identifies the risk factors, clinical profile, current burden and seasonal variation of rotavirus diarrhoea. It will be helpful in evaluating the impact of the rotavirus vaccine on the severity of the disease.